Music rights unveiled a filmmaker's guide to music rights and licensing - Wentz, Brooke; Battaglia, Maryam (Routledge, Taylor & Francis Group, 2018)
"Music Rights Unveiled provides an inside look at the complex world of music rights for film and video, and includes step-by-step guidance to navigate these tricky waters. Authors Brook Wentz and Maryam Battaglia share their decades of expertise in this user-friendly guide, designed specifically with filmmakers and producers in mind. The book provides a brief history of the pricing of music in film, television and digital media markets, and explains the process by which music is licensed or acquired for films, highlighting pitfalls to avoid and strategies for success" -- From back cover.